LIVING IN HARMONY:FINANCIAL REPORTING OBJECTIVE OF JAVANESE TRADITIONAL MARKET TRADERS - Wiyarni, Wiyarni; Triyuwono, Iwan; Ludigdo, Unti; Djamhuri, Ali (Accounting Department,, 2014)
Accounting conceptual framework consists of two main components, they are the objectives of financial reporting and the concepts that resultand follow logically from those objectives.Modern retail market usually uses this conceptual framework to prepare its financial reporting. The purpose of this study is to define the financial reporting objectives of Javanese traditional market traders who have different concept with modern retail market traders because they have different culture. This study uses grounded theory method to explore the accounting values of Javanese traditional market traders.Â Using 7 informants in 4 traditional markets in South of Malang, it is found that the feeling of grateful for whatever they got (nrimoingpandum) and great tolerance each other (among roso) as a foundation for their simple accounting reporting.Â This study comes with living in harmony as a financial reporting objective of Javanese traditional market trader. Key words: Javanese traditional market, grounded theory, living in harmony.